2020
DOI: 10.1029/2019ja027369
|View full text |Cite
|
Sign up to set email alerts
|

Examining Local Time Variations in the Gains and Losses of Open Magnetic Flux During Substorms

Abstract: The open magnetic flux content of the magnetosphere varies during substorms as a result of dayside and nightside reconnection. The open flux can be calculated from the area of the polar cap, delineated by the open-closed field line boundary (OCB). This study presents a superposed epoch analysis of the location of the OCB and the change in the magnetic flux content in individual nightside MLT sectors during substorm growth, expansion, and recovery phases. Far ultraviolet (FUV) observations from the IMAGE satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Recently, Mooney et al. (2020) studied the open‐closed field line boundary (OCB) movement during substorms based on IMAGE FUV images. It was found that within ∼10 min of the beginning of the substorms, in the MLT prior to the onset MLT sectors (MLT difference approximately from −4 to −1 h), the OCB moved equatorward due to the increasing open flux during the growth phase, while in the MLT sectors near and after the onset MLT (MLT differences from 0 to 4 h), the OCB tended to contract poleward or showed no changes in the latitude location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mooney et al. (2020) studied the open‐closed field line boundary (OCB) movement during substorms based on IMAGE FUV images. It was found that within ∼10 min of the beginning of the substorms, in the MLT prior to the onset MLT sectors (MLT difference approximately from −4 to −1 h), the OCB moved equatorward due to the increasing open flux during the growth phase, while in the MLT sectors near and after the onset MLT (MLT differences from 0 to 4 h), the OCB tended to contract poleward or showed no changes in the latitude location.…”
Section: Resultsmentioning
confidence: 99%
“…However, the previous study indicated that with activity increasing, the EB moved to lower latitudes at a faster rate in the post-noon sector, while the PB moved equatorward in the post-noon sector and poleward on the entire nightside statistically, which is different from the results here. Recently, Mooney et al (2020) studied the open-closed field line boundary (OCB) movement during substorms based on IMAGE FUV images. It was found that within ∼10 min of the beginning of the substorms, in the MLT prior to the onset MLT sectors (MLT difference approximately from −4 to −1 h), the OCB moved equatorward due to the increasing open flux during the growth phase, while in the MLT sectors near and after the onset MLT (MLT differences from 0 to 4 h), the OCB tended to contract poleward or showed no changes in the latitude location.…”
Section: Boundary Movementmentioning
confidence: 99%
“…Additionally, storm‐time reconnection is strong and can extend across a sizeable portion of the nightside oval, leading to a significant deformation of the assumed circular polar cap boundary. This deformation can lead to an overestimate of the open flux of the magnetosphere (Mooney et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We note that, in this example, there is a lack of observed auroral boundaries in some dayside MLT sectors. While the method of Longden et al (2010) aims to identify the poleward and equatorward auroral luminosity boundaries in each MLT sector, the number of successful boundary identifications in dayside sectors is much lower than on the nightside (Mooney et al, 2020). The dayside aurora tends to be dimmer and thinner (Carbary, 2005;Holzworth & Meng, 1975) and is more contaminated with dayglow making it more difficult to identify the dayside auroral boundaries.…”
Section: Observational Data: Auroral Boundaries Derived From Image Fuv Datamentioning
confidence: 99%
“…The solar wind driven OP-2013 model is unable to forecast substorm activity and the 30-min resolution of the operational forecasts cannot capture substorm dynamics, however, the change in width of the auroral oval during substorms occurs within the average predicted auroral oval location. Mooney et al (2020) showed that during substorms, the poleward boundary of the auroral oval moves by up to 3° in the substorm onset MLT sectors. During substorms, the typical width of the auroral oval varies by 10°-17° (Walach et al, 2017).…”
Section: Deterministic Auroral Forecastsmentioning
confidence: 99%